Medievalism and discrimination - Fugelso, Karl. (Cambridge : D.S. Brewer, 2019)
The difficult and nuanced issue of discrimination - race, gender, ethicity, religion - is the focus of this volume.
Work for the Soul: Medievalism, the Arts and Crafts Movement, and the Development of a Practical Spirituality in Evelyn Underhill's Novel The Gray WorldExhuming the Living Dead: The Anchoresses of Chris Newby and Robyn Cadwallader; The King's Speech: Battle Orations in Medieval Film; Horns: Vikings, Adaptation, Evolution; Bidding with Beowulf, Dicing with Chaucer, and Playing Poker with King Arthur: Neomedievalism in Modern Board-Gaming Culture; Vincent van Gogh, the Tre Corone, and the Studio of the South
Includes bibliographical references.
Print version record.
A Transcription of Helen Waddell's Notes on the Roman de la Rose and Christine de Pizan: Manuscript Queen's University Belfast 18/1/cContributors
JSTOR
Keywords: Medievalism; Discrimination -- History -- To 1500.; Médiévisme.; Discrimination -- Histoire -- Jusqu'à 1500.; Medievalism (cultural movement); Discrimination; Medievalism; To 1500; History